6-Hydroxy-5,6-seco-stemocurtisine: A novel seco-stemocurtisine-type alkaloid - Pitchaya Mungkornasawakul (2018)
A novel seco-stemocurtisine-type alkaloid, 6-hydroxy-5,6-seco- stemocurtisine was isolated from the aerial parts of Stemona curtisii (Stemonaceae) collected from Trang Province in Thailand. The unprecedented 5,6-seco-pyrido[1,2-a]azepine structure was elucidated by 2D NMR analysis and a single crystal X-ray crystallographic analysis. © 2013 Phytochemical Society of Europe. Published by Elsevier B.V. All rights reserved.